Comparison of effectiveness of various treatment strategies in COVID-19 patients: A Systematic Review - Muhammad Shehryar Hussain ,Ali Haider ,Usama Ahmad Yousuf ,Warisha Laraib ,Fatima Dildar ,Hafiz Amjad Hussain (Journal of Rawalpindi Medical College, 2020)
Background: The purpose of this study is to systematically review the effectiveness of various drugs and therapies by assessing already conducted studies on COVID-19 patients. Methods: The eligibility criterion for this systematic review was to include the observational and experimental studies including case reports; conducted on the possible treatments of COVID-19. Only those studies were included that were written in the English language either published or unpublished from December 2019 to April 10, 2020. Quality of articles was assessed and flawed studies were excluded based on incomplete outcome data. Treatment strategies experimented on animals or those assessed through artificial intelligence were also excluded. The databases searched were PubMed, Google Scholar, Cochrane Library, and bioRxiv. The last date to search the databases was April 10, 2020. Results: We selected 25 articles which include 12 case studies, 10 retrospective studies, one randomized controlled trial, one non-randomized Controlled trial, and one prospective observational study. Hydroxychloroquine proved to be effective in all three studies under consideration especially when it was used in a combination with azithromycin. Antivirals showed significant results in eleven out of sixteen studies. The remaining five studies showed antiviral therapy to be ineffective. Lopinavir/ritonavir did not show satisfactory results in most of the COVID-19 patients. Both of the studies regarding convalescent plasma therapy showed significant improvement in patients undergoing treatment. Two studies regarding treatment with immunoglobulins also showed good results. A study on the use of Mesenchymal stem cell transplant for treatment of COVID-19 patients also proved to be effective. Likewise, a study on the use of Traditional Chinese Medicine along with Western Medicine also showed good results. In patients of organ transplant, withdrawal of immunosuppressive drugs, and the use of methylprednisolone along with antivirals had shown significantly good results. Among all these therapeutic approaches we found convalescent plasma therapy to be most effective. Conclusion: So far, a small number of studies have been conducted on the treatment of COVID-19 patients and most of them were conducted on the Chinese population. More randomized controlled trials are needed to evaluate the effectiveness of different treatment strategies at a broader level.